Mandating teaching approaches stifles innovation: a case against - Luqman Baehaqi (Journal on English as a Foreign Language, 2022)
The article discusses the primacy of Systemic Functional Linguistics (SFL) in research and pedagogy on second language (L2) writing in Indonesia. Indonesian academics use SFL theory as a shell to value arguments and observations in the methodological literature of L2 writing, demonstrating how the theory transforms into an "instrument reliable for scaffolding thinking, for propelling knowledge and ideas forward" (Thomas, 2007, p. 44) in their research and practice. The hijacking of an educational researcher's thought process and methodology by a linguistic paradigm serves only to reinforce the researchers' lack of confidence in challenging the established and recognized paradigm. Numerous articles from reputable local publications were gathered and analyzed. The paper concludes that researchers working in Indonesiashould commit to conducting more thought experiments to learn and support critical refection over and above imitating “what has been". Reflection and consideration of interdisciplinary evidence help make a unique contribution to educational theory and practice.